Problems of Direct Composite Posterior Restorations: A Clinical Study - Susanne Gerhardt-Szep; Elke Schröder-Schichtel; Quanita Zücker; Tugba Zahn; Stefanie Feierabend; Stefan Rüttermann (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
The aim of this clinical study was to describe the quality of posterior composite restorations (n = 329) performed on a group of patients (n=219) during an observation period of three years at various intervals (6, 12, 18, 24 and 36 months) after application. The parameters were assessed both In vivo and In vitro using clinical examinations, impressions and photography according to modified FDI criteria. For the statistical analysis of the results, the Wilcoxon test with a significance level of p = 0.05 was applied. After three years, In vivo five from the seven parameters exhibited significant changes. Only "retention" and "approximal contact" remained unchanged. In vitro studied parameters "anatomical form", "occlusal contour/wear" and "approximal contact" did not result in any significant changes, however "marginal adaptation", "surface luster" and "overhangs" deteriorated significantly. In summary, the results of this study show that composite posterior restorations were clinically acceptable in terms of specific parameters. However, unsatisfactory results have arisen in relation to the handling of composites, stated In vivo and In vitro especially in the reconstruction of the marginal adaptation, surface and overfilling.